Employee Data (Data Requirements, Data Collection Activities And Information Systems) Educational Human Resource Management Study - Najmi Muhajir, Nur Muhammad; Zohriah, Anis (Mudir : Jurnal Manajemen Pendidikan, 2024)
Employee data is a collection of data that includes a list of workers in a factory or company starting with the start of work, salary, retirement or, as we know, the end of a person's work. Like teachers, doctors, factory employees. Employee data needs can be done through analysis of positions and workload requirements. An information system is a tool for presenting information in accordance with the vision to be achieved so that it is useful. There are three components in the system or in other words basic functions that actively interact first,: Input. Second, Process. Third, Output (output). By creating an organized and neatly computerized system, the processing of employee data and employee information can be carried out smoothly and provide sufficiency to parties who need this information. This article is included in qualitative research with a library research approach. Research carried out by the author in the library to obtain theoretical data. In this case, what must be paid attention to is the object being studied, namely in particular the reading books which are the subject of discussion and interconnectedness in existing problems.